DYNAMIC STABILITY OF WAVE PROCESSES OF A ROUND ROD - Seitmuratov Angisin; Zhussipbek Botagoz Kunibekkyzy; Sydykova Gulnar; Ainur Seitkhanova; Aitimova Ulzada Zholdasbekovna (Academic Scientific Journal of Computer Science, 2019)
This paper is devoted to the study of the stability dynamics of wave processes of flat and circular elements, and also some axisymmetric problems of oscillation of an elastic layer limited by rigid or deformable boundaries when exposed to normal or rotational shear stresses are considered. Solutions to the problems under consideration were obtained using integral transformations by coordinate or time. The work develops the dynamic stability of a round rod. The loss of stability of a round rod will be investigated on the basis of the mathematical theory and the transverse oscillations of a round rod, described in the work of I.G. Philippov.